Pengaruh Good Corporate Governance (GCG) Terhadap Related Party Transaction (RPT) pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2022 - Vinnie Setia Anggraini; Rihfenti Ernayani; Ita Yuni Kartika (Yayasan Almanar Pujud, 2024)
The purpose of this study is to determine the effect of independent commissioners, audit committees, and institutional ownership on Related Party Transaction Assets & Liabilities (RPTAL) in Non-Financial Companies listed on the Indonesia Stock Exchange (IDX) in 2022. The data used are existing sources, both internal and external data, and data can be accessed via the internet and information publications. The data used are financial reports of non-financial companies published on the Indonesia Stock Exchange for the 2022 period. The data analysis method uses multiple linear regression. The results of this analysis indicate that Independent Commissioners have no effect on Related Party Transaction Assets (RPTAL) in non-financial companies in 2022. The Audit Committee has a negative effect on Related Party Transaction Assets (RPTAL) in non-financial companies in 2022. Institutional Ownership has a negative effect on Related Party Transaction Assets (RPTAL) in non-financial companies in 2022.